Detection of a large spectrum of viral infections in conjunctival premalignant and malignant lesions. Issue 10 (6th July 2020) - Galati, Luisa; Combes, Jean Damien; Gupta, Purnima; Sen, Rajdip; Robitaille, Alexis; Brancaccio, Rosario Nicola; Atsou, Kueshivi; Cuenin, Cyrille; McKay‐Chopin, Sandrine; Tornesello, Maria Lina; Buonaguro, Franco Maria; Clifford, Gary; et al.
Abstract: To study the interaction between HIV and other carcinogenic infections in conjunctival squamous cell carcinoma (SCC), we evaluated the presence of a broad spectrum of human viruses in conjunctiva specimens. Beta Human papillomavirus (HPV; n = 46), gamma HPV (n = 52), polyomaviruses (n = 12) and herpes viruses (n = 3) was determined in DNA extracted from 67 neoplastic and 55 non‐neoplastic conjunctival tissues of HIV‐positive and HIV negative subjects by Luminex‐based assays. Next‐generation sequencing (NGS) was also used to further characterize the presence of cutaneous HPVs. Detection of beta‐2 HPV infections was associated with the risk of neoplasia (adjusted odds ratio [aOR] 3.0; 95% confidence interval [CI] 1.3‐6.8), regardless of HIV status (HIV positive, aOR 2.6, 95% CI 0.9‐7.7; HIV negative, aOR 3.5, 95% CI 0.9‐14.4). EBV was strongly associated with the risk of neoplasia (aOR 12.0, 95% CI 4.3‐33.5; P  < .01) mainly in HIV individuals (HIV positive, aOR 57.5; 95% CI: 10.1‐327.1; HIV negative aOR 2.6; 95% CI: 0.2‐34.7). NGS allowed to identify 13 putative novel HPVs in cases and controls. Our findings suggest a role of beta HPV types and EBV, in conjunctival SCC. However, additional studies of viral expression in tumor tissue are required to confirm the causal association. Abstract : What's new? Risk of conjunctival squamous cell carcinoma (SCC) is strongly associated with ultraviolet radiation exposure and immune suppression. In Africa, SCC incidence has also been affected by the spread of HIV and may be impacted by other viral infections. Here, analyses of a large number of viruses in conjunctival non‐malignant and malignant tissues from patients in Southern Uganda reveal associations between conjunctival SCC and cutaneous beta human papillomavirus (HPV) and Epstein‐Barr virus (EBV) infection. Beta‐2 HPV infection was linked to neoplasia risk regardless of HIV status, whereas EBV was associated with neoplasia primarily in HIV‐infected individuals.